Resposta da cultura do milho aos fertilizantes fosfatados e nitrogenados revestidos com polímeros - Machado, Vanessa Júnia (2012)
The effective use of fertilizers, besides resulting in greater yield, can reduce production costs, with positive results in the end of the cropping season. Soil correction and fertilization in intensive maize production systems represent, on average, 40% to 45% of the production cost. Phosphorus is considered as a nutrient with low absorption by plants due to fixation reaction with the soil, since the anion H2PO4 - presents great affinity for the surface of iron and aluminum colloid oxides. Nitrogen in soil is predominantly in the organic form. Inorganic fractions are formed by NH4 + and, mostly, NO3 - in well drained soils. In order to reduce losses and increase yield economically and sustainably, using P and N sources, slow release formulations were developed, allowing to reduce losses that usually occur with the use of urea and triple Superphosphate, thus allowing a more effective use of fertilizers without affecting crop yield. Polymerized fertilizers can be of slow release, gradually supplying nutrients to the plants. Therefore, lower application frequency would be required; reducing labor costs with splitting fertilization, avoid damage to seeds and roots due to excessive fertilization, and are less susceptible to losses, reducing the risk of environmental pollution. This study evaluated agricultural and economic efficacy of conventional and polymer-covered phosphate and nitrogen fertilizer sources in no-till maize, in Patos de Minas, region of Alto Paranaíba in Minas Gerais. Increased yield was observed in the experiment with polymer-covered superphosphate triple in relation to the conventional one. Economic return was observed until the dose of 90 kg ha-1 with the polymer-covered fertilizer. In contrast, best results were observed with conventional urea application.